Imaging metals in Caenorhabditis elegans. Issue 4 (5th January 2017) - Aschner, M.; Palinski, C.; Sperling, M.; Karst, U.; Schwerdtle, T.; Bornhorst, J.
Abstract : Possible analytical imaging approaches and their advantages and disadvantages for the study of metal (M) distribution in C. elegans . Abstract : Systemic trafficking and storage of essential metal ions play fundamental roles in living organisms by serving as essential cofactors in various cellular processes. Thereby metal quantification and localization are critical steps in understanding metal homeostasis, and how their dyshomeostasis might contribute to disease etiology and the ensuing pathologies. Furthermore, the amount and distribution of metals in organisms can provide insight into their underlying mechanisms of toxicity and toxicokinetics. While in vivo studies on metal imaging in mammalian experimental animals are complex, time- and resource-consuming, the nematode Caenorhabditis elegans ( C. elegans ) provides a suitable comparative and complementary model system. Expressing homologous genes to those inherent to mammals, including those that regulate metal homeostasis and transport, C. elegans has become a powerful tool to study metal homeostasis and toxicity. A number of recent technical advances have been made in the development and application of analytical methods to visualize metal ions in C. elegans . Here, we briefly summarize key findings and challenges of the three main techniques and their application to the nematode, namely sensing fluorophores, microbeam synchrotron radiation X-ray fluorescence as well as laser ablation (LA) coupled to inductively coupled plasma-mass spectrometry (ICP-MS).